Epinephrine administration for adult out-of-hospital cardiac arrest patients with refractory shockable rhythm: time-dependent propensity score-sequential matching analysis from a nationwide population-based registry. Issue 3 (23rd February 2021) - Matsuyama, Tasuku; Komukai, Sho; Izawa, Junichi; Gibo, Koichiro; Okubo, Masashi; Kiyohara, Kosuke; Kiguchi, Takeyuki; Iwami, Taku; Ohta, Bon; Kitamura, Tetsuhisa
Abstract: Aims: Little is known about the effect of prehospital epinephrine administration in out-of-hospital cardiac arrest (OHCA) patients with refractory shockable rhythm, for whom initial defibrillation was unsuccessful. Methods and results: This study using Japanese nationwide population-based registry included all adult OHCA patients aged ≥18 years with refractory shockable rhythm between January 2014 and December 2017. Patients with or without epinephrine during cardiac arrest were sequentially matched using a risk set matching based on the time-dependent propensity scores within the same minute. The primary outcome was 1-month survival. The secondary outcomes included 1-month survival with favourable neurological outcome (cerebral performance category scale: 1 or 2) and prehospital return of spontaneous circulation (ROSC). Of the 499 944 patients registered in the database during the study period, 22 877 were included. Among them, 8467 (37.0%) received epinephrine. After time-dependent propensity score-sequential matching, 16 798 patients were included in the matched cohort. In the matched cohort, positive associations were observed between epinephrine and 1-month survival [epinephrine: 17.3% (1454/8399) vs. no epinephrine: 14.6% (1224/8399); RR 1.22 (95% confidence interval, CI: 1.13–1.32)] and prehospital ROSC [epinephrine: 22.2% (1868/8399) vs. no epinephrine: 10.7% (900/8399); RR 2.07 (95% CI: 1.91–2.25)]. No significant positive association was observed between epinephrine and favourable neurological outcome [epinephrine: 7.8% (654/8399) vs. no epinephrine: 7.1% (611/8399); RR 1.13 (95% CI 0.998–1.27)]. Conclusion: Using the nationwide population-based registry with time-dependent propensity score-sequential matching analysis, prehospital epinephrine administration in adult OHCA patients with refractory shockable rhythm was positively associated with 1-month survival and prehospital ROSC.